Women in Indian politics - Raj, Kalpana (Delhi Rajat, 1999)
Women in Indian politics have been an active participants in every Indian election. To be sure that women have been highly visible participants, they have served in both houses of parliament and in the state legislatures been governors and chief ministers
Keywords: Women in politics-India; Politics, Practical